Sikkim State Annual Plan 1998-99 - Planning Commission (Planning Commission, 1999)
The broad strategy to be followed as far as Sikkim is concerned during the Ninth Five Year Plan has been outlined in the main document containing the proposals for the State during the period 1997-2002. The interalia indicates that the Slate would be aiming at a growth rale of 10% per annum by stepping up the quantum of investment, improvement in the efficiency with which capital is being utilised, achieving self-reliance in various sectors, improvement of productivity standards and improving the efficiency in the utilisation of human and capital resources.
Planning and development departmen government of sikkim gangtok